Non-universality of leptons as a source of new physics from tree level interactions of pseudoscalar mesons - Wasi Uz Zaman; Shakeel Mahmood; Abrar Ahmad; Maimoona Razzaq; Kamran Hussain Tahir (Kuwait Journal of Science)
This article is based on the study of pure leptonic decays of charged pseudoscalar mesons taking non-universality into account. We calculate the branching ratios of the processes 𝜋 ±, 𝐾±, 𝐷±, 𝐷±𝑠, 𝐵±. For the search for new physics (NP), we examine the discrepancies between theoretical and experimental results. The discrepancies are possibly due to massive neutrinos, processed massless in the Standard Model (SM), and universal coupling of leptons. We focus on the non-universality of leptons in order to find the bounds on Non-Standard Interaction (NSI) parameters 𝜀. We use charge current like NSI and conclude that these decays could provide strong constraints on the NSI parameter.